2013
DOI: 10.1016/j.ejphar.2013.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effect of mirtazapine mediates its effect in the median raphe nucleus

Abstract: Mirtazapine, a noradrenergic and specific serotonergic antidepressant (NaSSA), blocks the α 2 -adrenergic autoreceptors and heteroreceptors, which are responsible for controlling noradrenaline and 5-hydroxytryptamine (5-HT) release. Though preclinical and clinical studies have shown that mirtazapine exerts an anxiolytic action, its precise brain target sites remain unclear. In the present study, we investigated the brain area(s) in which mirtazapine exerts its anxiolytic-like effects on the expression of conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several research studies have suggested that mirtazapine decreases anxiety-like behavior in the EPM and depression-like behaviors in the FST in animals treated with saline (An et al, 2013, 2015, 2016a, 2016b; Kaminska and Rogoz, 2016; Rogóż, 2010, 2012; Rogóż et al, 2012). We found similar results: in animals dosed with 30 mg mirtazapine, anxiety-like (as measured in the EPM test, OFT and the LDT) and depression-like behaviors (according to the FST) decreased after 15 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have suggested that mirtazapine decreases anxiety-like behavior in the EPM and depression-like behaviors in the FST in animals treated with saline (An et al, 2013, 2015, 2016a, 2016b; Kaminska and Rogoz, 2016; Rogóż, 2010, 2012; Rogóż et al, 2012). We found similar results: in animals dosed with 30 mg mirtazapine, anxiety-like (as measured in the EPM test, OFT and the LDT) and depression-like behaviors (according to the FST) decreased after 15 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10 Its action mainly affects the median raphe nucleus. 11 This nucleus is formed by abundant serotonergic cells that project to the forebrain, mainly to limbic areas of the prosencephalon that control emotional behaviour. It also projects extensively to the hippocampus, regulating memory and regulating dopaminergic activity in the forebrain.…”
Section: Introductionmentioning
confidence: 99%
“…Mirtazapine has been shown in laboratory rodents to act as an anxiolytic through its effect on 5‐HT1a and α‐1 receptors 10 . Its action mainly affects the median raphe nucleus 11 . This nucleus is formed by abundant serotonergic cells that project to the forebrain, mainly to limbic areas of the prosencephalon that control emotional behaviour.…”
Section: Introductionmentioning
confidence: 99%